2020
DOI: 10.1002/jez.2342
|View full text |Cite
|
Sign up to set email alerts
|

Resource availability and its effects on mother to embryo nutrient transfer in two viviparous fish species

Abstract: Different hypotheses have been proposed to explain the adaptive value of matrotrophy, which is the postfertilization maternal provisioning to developing embryos. The Trexler–DeAngelis model proposes that matrotrophy provides fitness advantages when food abundance is high and availability is constant. If food availability is low or unpredictable, prefertilization maternal provisioning (lecithotrophy) should be favored over matrotrophy. In this study, we tested this model in two fish species from the family Poec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…High-predation sites are triangles; low-predation sites are circles. the specimens, an approach that has been applied widely across life history studies, including in our previous work (Johnson and Belk, 2001;Belk et al, 2011;Brown et al, 2018;Molina-Moctezuma et al, 2020), thus allowing us to compare findings here with previous work. We collected life history data using methods described in Johnson and Belk (2001).…”
Section: Life Historymentioning
confidence: 99%
“…High-predation sites are triangles; low-predation sites are circles. the specimens, an approach that has been applied widely across life history studies, including in our previous work (Johnson and Belk, 2001;Belk et al, 2011;Brown et al, 2018;Molina-Moctezuma et al, 2020), thus allowing us to compare findings here with previous work. We collected life history data using methods described in Johnson and Belk (2001).…”
Section: Life Historymentioning
confidence: 99%
“…The studies that have tested the Trexler-DeAngelis model of maternal provisioning have yielded mixed results, which may be attributed to different methodologies. Some studies were based on laboratory experiments (Marsh-Matthews and Deaton, 2006;Pires et al, 2007;Banet and Reznick, 2008;Banet et al, 2010;Pollux and Reznick, 2011;Itonaga et al, 2012;Van Dyke et al, 2014;Molina-Moctezuma et al, 2020), whereas others were conducted under natural conditions Travis, 2008, 2012;Riesch et al, 2013;Molina-Moctezuma et al, 2020). In controlled experiments, the amount of food and fluctuations in its availability are the only variables at play.…”
Section: Future Directionsmentioning
confidence: 99%
“…alvarezi), whereas other species exhibit extensive matrotrophy (e.g., Poecilia parae and Poeciliopsis prolifica), with several species showing varying degrees of the relative amounts of pre-and post-fertilization provisioning (Reznick et al, 2002;Pires et al, 2007Pires et al, , 2010Pollux et al, 2009;Pollux and Reznick, 2011;Torres-Mejia, 2011;Olivera-Tlahuel et al, 2015). In addition, some studies have demonstrated that the degree of matrotrophy (i.e., the amount of postfertilization maternal provisioning) may also vary among different populations of the same species (Reznick et al, 2007;Turcotte et al, 2008;Pires et al, 2010;Molina-Moctezuma et al, 2020). Due to the large variation in the way poeciliid females provide resources to their embryos, some studies have attempted to understand the potential benefits of matrotrophy over lecithotrophy DeAngelis, 2003, 2010;Pollux et al, 2009Pollux et al, , 2014Saleh-Subaie and Zúñiga-Vega, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations